PENERAPAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN MINAT MENGHAFAL AL-QURAN SURAT AN-NASR HINGGA SURAT AN-NASS DI DTA AL-IKHLAS - Dewi Fitriani; Siti Masruroh; Mitra Sasmita (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to determine the Application of Audio Visual Media in Increasing Interest in Memorising Al-Quran Surah An-Nasr to Surah An-Nas. By using a qualitative approach with a case study, this research involves teachers and students as the main subjects. The data taken in the form of interviews, as well as direct observation at school, and documentation which was then analysed thematically. The result of this study is that audio visual media can increase the interest in memorising the Qur'an from Surah An-Nasr to Surah An-Nas. However, internal and external obstacles such as limited teacher skills in utilising the media.